2020
DOI: 10.21608/dsu.2020.14819.1005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Shear Bond Strength of Two Types of Adhesive Resin Cements to Zirconia after Surface Treatment using Silica Coating

Abstract: Aim: to evaluate the shear bond strength of zirconia bonded with two self etch adhesive resin cements PANAVIA F 2.0 and BISTITE ΠDC using two surface treatment techniques: sand blasting and silica coating using Cojet system. Materials and Methods: Twenty rectangular samples with dimensions (14.5×13×3.6mm) and twenty samples with dimensions (7.2×6×3.6mm) were cut from three zirconia ceramic blocks. Sandblasting was done using air blasting machine with 110 µm AL 2 O 3 particles and Silica coating surface treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Regarding fracture resistance, the results of this study showed significantly higher values for the control group, which could be explained by the difference in the processing technique and veneering material [29]. Groups A and B showed no significant differences with slightly higher values in groups B, which could be attributed to the fact that sandblasting with silica coating embeds silica particles in the surface of the substrate, producing a physically and chemically active outer surface layer (oxide layer), which promotes a chemical adhesion with the phosphate monomer (MDP), resulting in a stronger bonding [30]. It is worth mentioning that all specimens exhibited higher values than the average bite force in the first molar region, as documented by Khan et al [31].…”
Section: Discussionmentioning
confidence: 97%
“…Regarding fracture resistance, the results of this study showed significantly higher values for the control group, which could be explained by the difference in the processing technique and veneering material [29]. Groups A and B showed no significant differences with slightly higher values in groups B, which could be attributed to the fact that sandblasting with silica coating embeds silica particles in the surface of the substrate, producing a physically and chemically active outer surface layer (oxide layer), which promotes a chemical adhesion with the phosphate monomer (MDP), resulting in a stronger bonding [30]. It is worth mentioning that all specimens exhibited higher values than the average bite force in the first molar region, as documented by Khan et al [31].…”
Section: Discussionmentioning
confidence: 97%
“…The long-term effectiveness of all ceramic restorations depends on a strong and durable bond between the tooth structure, luting cements, and ceramics [35]. Sandblasting was used to treat the fitting surfaces of the crowns because it is thought to create surface roughness and irregularities, increase the surface wettability of the ceramic surface, and clean the substrate's surface, allowing the resin cement to flow into the surface [36].…”
Section: Discussionmentioning
confidence: 99%